S18 The association of cough-related quality-of-life, cough symptom scores and cough reflex sensitivity with markers of disease control in severe asthma. (December 2018) - Holmes, J; Heaney, L; Birring, S; McGarvey, L
Abstract : Background: Although cough is a common and troublesome symptom in asthma, clinicians do not routinely assess its impact or severity. A more comprehensive approach to cough may be of particular relevance in severe asthma where poor symptom control often leads to escalation in corticosteroid therapy. Objectives: In this study, we aim to assess the role of cough in patients with severe refractory asthma using cough-related patient reported outcome measurement tools. Here we present preliminary data from our first nineteen patients. Methods: Nineteen severe asthmatic patients were assessed using five cough measurement tools consisting of the Leicester Cough Questionnaire (LCQ), Cough-Specific Quality-of-life Questionnaire (CQLQ), and Visual Analogue Scales for cough severity (VASc) and urge to cough (VASu). In addition, a cough challenge was performed, with cough responses assessed for the concentration of citric acid needed to evoke two (C2 ) or five (C5 ) coughs. Results were compared with scores from the Asthma Control Questionnaire – 5 (ACQ-5) and Mini Asthma Quality of Life Questionnaire (Mini AQLQ). Results: Our preliminary analysis shows that scores from the LCQ and CQLQ have a strong inverse relationship in this population (rs =−0.69, p≤0.01). Scores from the LCQ demonstrated a very strong association with both the ACQ-5 (rs =−0.88, p≤0.01) and Mini AQLQ (rs =0.83, p<0.01). In a similar fashion, CQLQ scores show a moderate association with the ACQ-5 (rs =−0.58, p≤0.01) and a strong association with the Mini AQLQ (rs =−0.67, p<0.01). VASc scores were moderately correlated with ACQ-5 (rs =0.47, p=0.04) and Mini AQLQ (rs =−0.49, p=0.04). Additionally, VASu scores also show a stronger relationship with ACQ-5 (rs =0.54, p=0.02) and Mini AQLQ (rs =−0.62, p<0.01). Finally, no significant associations were observed between C2 or C5 endpoints and any other study measurements. Conclusion: Despite not being extensively considered in the assessment of severe asthma, cough may be a driving component of asthma control and asthma-related quality-of-life.